ANCA-Positive pauci-immune crescentic glomerulonephritis in a patient with systemic lupus erythematosus - Herrera-Añazco,Percy (2017)
Abstract The pauci-immune crescentic glomerulonephritis (PICGN) is generally associated with small-vessel vasculitis with a few reported cases associated with other autoimmune diseases such as Systemic Lupus Erythematosus (SLE). We present the case of a female 34-year-old patient with acute kidney injury symptoms with indication for renal replacement therapy in the context of clinical SLE diagnosis. A kidney biopsy was conducted and it was found that most glomeruli showed some segmental sclerosis with synechia to the Bowman's capsule. 67% of the glomeruli had fibroepithelial crescents. Moreover, the interstitial space had a moderate lymphomononuclear infiltration and mild fibrosis. In the arterioles, there were walls thickened by subintimal sclerosis. Direct immunofluorescence detected limited IgM and C3 deposits in capillary loops and negative mensangium for IgG, IgA and C1q. A therapy using corticosteroids and intravenous cyclophosphamide was initiated with stable evolution. PICGN associated with SLE is a rare pathology with clinical presentation, varied evolution and without a standard medical treatment.